Novel monoclonal antibodies against Fiber-1 of duck adenovirus 3 and their B cell epitopes - Shao, Hongxia; Zhang, Wenyuan; Lin, Yun; Xie, Jing; Ren, Dan; Xie, Quan; Li, Tuofan; Wan, Zhimin; Qin, Aijian; Ye, Jianqiang (Frontiers in Veterinary Science, 2022)
Recently, the outbreak of the infection of Duck adenovirus 3 (DAdV-3) characterized by swelling and hemorrhagic liver and kidney has caused huge economic losses to duck industry since 2014 in China. To date, the B cell epitopes in the Fiber-1 protein and the underlying infection mechanism of DAdV-3 have not been investigated. In this study, the recombinant Fiber-1 protein was first expressed in E.coli and six novel monoclonal antibodies (mAbs) against Fiber-1 were generated, designated as 1D8, 1E6, 3G6, 4G1, 4G2 and 6F10, respectively. Moreover, mAbs 3G6 and 6F10 could efficiently immunoprecipitate the Fiber-1 in LMH cells infected with DAdV-3 or transfected with pcDNA3.1-Fiber-1. Notably, mAbs 3G6 and 4G2 also showed certain neutralizing activity against DAdV-3 infection in vitro. Epitopes mapping revealed that the B cell epitope recognized by 6F10, 3G6, 4G1, 1D8, 4G2 and 1E6 was located in 34-66aa, 67-99aa, 64-296aa, 297-329aa, 330-362aa and 363-395aa, respectively. Sequence alignments further found that the six epitopes recognized by these mAbs were highly conserved among different DAdV-3 isolates. The generated mAbs specific to Fiber-1 and their defined epitopes provide powerful tools for establishing rapid and efficient diagnostics for the detection of DAdV-3 and pave the way for further studying on the critical role of Fiber-1 in mediating the infection of DAdV-3.